Elderly Participation in Religious Activities: An Analysis of Domestic Barriers and Social Support: Partisipasi Lansia dalam Kegiatan Keagamaan: Telaah Hambatan Domestik dan Dukungan Sosial - Adika Hary Hermawan; Andi Arif Rifa`i (RADIANT: Journal of Applied, Social, and Education Studies, 2026)
This Study aims to identify domestic barriers that affect the participation of elderly people in regular recitation at the Nurul Qolbi Islamic Council and formulate strategies to overcome them. The method used is a descriptive qualitative approach with data collection techniques through semi-structured interviews, observation, and documentation. Informants consisted of elderly congregants, majelis taklim administrators, and family members. The findings of this study indicate that elderly participation is influenced by various domestic barriers such as the dual roles of the elderly, health factors, dependence on companions, weather factors, and environmental safety. This is supported by adaptive strategies for individual elderly people, family support, majelis taklim administrators, and community-based strategies. This study shows that these domestic barriers shape patterns of elderly attendance that are not always consistent, supported by strategies that can increase the consistency of the elderly in attending regular religious lectures.